Comparative Statics in Dynamic Programming Models with an Application to Job Search - James W. Albrecht; Bertil Holmlund; Harald Lang (The Research Institute of Industrial Economics (IUI), 1986)
This paper presents a technique for qualitative comparative statics analysis in dynamic programming models. Let the value function v be the fixed point of a contraction mapping which depends differentially on some exogenous parameter theta. Then the derivative of v with respect to theta exists and is also the fixed point of a contraction mapping. Since this derivative is the fixed point of a contraction mapping its qualitative properties can be investigated using mathematical induction. This comparative statics methodology is illustrated with an application to a model of job search.
Keywords: C61; J60; 330; Qualitative comparative statics analysis; dynamic programming; job search model; Arbeitsmarkt